Sulfation of Quercitrin, Epicatechin and Rutin by Human Cytosolic Sulfotransferases (SULTs): Differential Effects of SULT Genetic Polymorphisms - Mei, Xue; Gohal, Saud A.; Alatwi, Eid S.; Hui, Ying; Yang, Chunyan; Song, Yongyan; Zhou, Chunyang; Liu, Ming-Cheh (Planta Medica, 2021)
Radix Bupleuri is one of the most widely used herbal medicines in China for the treatment of fever, pain, and/or chronic inflammation. Quercitrin, epicatechin, and rutin, the flavonoids present in Radix Bupleuri, have been reported to display anti-inflammatory, antitumor, and antioxidant biological activities among others. Sulfation has been reported to play an important role in the metabolism of flavonoids. In this study, we aimed to systematically identify the human cytosolic sulfotransferase enzymes that are capable of catalyzing the sulfation of quercitrin, epicatechin, and rutin. Of the thirteen known human cytosolic sulfotransferases, three (cytosolic sulfotransferase 1A1, cytosolic sulfotransferase 1C2, and cytosolic sulfotransferase 1C4) displayed sulfating activity toward quercitrin, three (cytosolic sulfotransferase 1A1, cytosolic sulfotransferase 1A3, and cytosolic sulfotransferase 1C4) displayed sulfating activity toward epicatechin, and six (cytosolic sulfotransferase 1A1, cytosolic sulfotransferase 1A2, cytosolic sulfotransferase 1A3, cytosolic sulfotransferase 1B1, cytosolic sulfotransferase 1C4, and cytosolic sulfotransferase 1E1) displayed sulfating activity toward rutin. The kinetic parameters of the cytosolic sulfotransferases that showed the strongest sulfating activities were determined. To investigate the effects of genetic polymorphisms on the sulfation of quercitrin, epicatechin, and rutin, individual panels of cytosolic sulfotransferase allozymes previously prepared were analyzed and shown to display differential sulfating activities toward each of the three flavonoids. Taken together, these results provided a biochemical basis underlying the metabolism of quercitrin, epicatechin, and rutin through sulfation in humans.
Keywords: Bupleurum scorzonerifolium; Apiaceae; quercitrin; epicatechin; rutin; sulfation; cytosolic sulfotransferase; SULT; single nucleotide polymorphism; SNP